Professional C++ - Gregoire, Marc (Software engineer) (Wrox, a Wiley brand, 2018)
Get up to date quickly on the new changes coming with C++17 Professional C++ is the advanced manual for C++ programming. Designed to help experienced developers get more out of the latest release, this book skims over the basics and dives right in to exploiting the full capabilities of C++17. Each feature is explained by example, each including actual code snippets that you can plug into your own applications. Case studies include extensive, working code that has been tested on Windows and Linux, and the author's expert tips, tricks, and workarounds can dramatically enhance your workflow. Even many experienced developers have never fully explored the boundaries of the language's capabilities; this book reveals the advanced features you never knew about, and drills down to show you how to turn these features into real-world solutions. The C++17 release includes changes that impact the way you work with C++; this new fourth edition covers them all, including nested namespaces, structured bindings, string_view, template argument deduction for constructors, parallel algorithms, generalized sum algorithms, Boyer-Moore string searching, string conversion primitives, a filesystem API, clamping values, optional values, the variant type, the any type, and more. Clear explanations and professional-level depth make this book an invaluable resource for any professional needing to get up to date quickly. Maximize C++ capabilities with effective design solutions Master little-known elements and learn what to avoid Adopt new workarounds and testing/debugging best practices Utilize real-world program segments in your own applications C++ is notoriously complex, and whether you use it for gaming or business, maximizing its functionality means keeping up to date with the latest changes. Whether these changes enhance your work or make it harder depends on how well-versed you are in the newest C++ features. Professional C++ gets you up to date quickly, and provides the answers you need for everyday solutions.